ENHANCING THE PROPERTIES OF CONCRETE BY USING ALKALINE SOLUTION AND ITS COMPARATIVE STUDY WITH CONVENTIONAL CONCRETE - S. J. Aher; S.P. Mandhare; S.S. Ghawate; R. Gite; Prof.A. H. Jamale (International Journal of Innovations in Engineering Research and Technology, 2024)
The main aim of this project was to reduce the use of cement so as to produce a CO2 emission free cementitious material and Geopolymer Concrete (GPC) was the best alternative solution present out there. GPC utilizes industrial waste material such as fly ash from thermal power station to provide practical solution to waste management as well as environmental protection method. In this study we have used low calcium fly ash (ASTM class F), along with fly ash, water was enable to bind effectively. Therefore we also have replaced water completely with alkaline solution to hold fly ash, aggregate and sand together. The alkaline solutions we have used are – sodium hydroxide (NaOH) and sodium silicate (Na2SiO3). The main purpose to introduce alkaline solution was polymerization. That is the reason scientist Davidovits named this mix as geopolymer concrete. GPC required high temperature for curing to happen the polymerization, Thus, the curing of GPC was done at ambient temperature without keeping it in water unlike the conventional concrete. Amongst both the alkali solutions i.e. NaOH and Na2SiO3, sodium hydroxide was used in different molar concentration of 10M, 12M and 14M with keeping silicate to hydroxide ratio constant as 1.5, three different sets of 9 cubes, 3 beams and 3 cylinders were casted.